(untitled) (Semiárida, 2025)
Zooplankton organisms, especially copepods, play a fundamental role as trophic support for marine ecosystems and are also considered good indicators of environmental quality. In this context, the objective of this work was to determine and comparatively analyze the specific richness (r), Shannon-Wiener diversity (H´) and natural mortality of copepods in the zooplankton community in three areas with different degrees of anthropogenic alteration. For this purpose, the selected areas were Puerto Cuatreros-C, Puerto Ing. White-W (both located in the main navigation channel of the Bahía Blanca estuary), and Puerto Rosales-R (100 m from sewage discharge of Punta Alta city), during the winter period of 2019. Zooplankton samples were taken, stained, and preserved using neutral red intravital staining for subsequent qualitative and quantitative analysis under stereoscopic microscope. Non-predatory mortality was assessed through the incidence of dead copepods (ICM, expressed as a % of total copepod abundance), which was determined by observing intravital coloration. Our results showed that the zooplankton community was alternately dominated by the copepods Acartia tonsa and Eurytemora americana. The highest specific richness was found at site C (r = 12), and the lowest average diversity (H´ = 0.93), along with the lowest community abundance, were recorded at R (122.20 ± 148 ind m-3; Kruskal-Wallis p = 0.052). The average ICM by species were: 78.13 % for A. tonsa, 72.43 % for Euterpina acutifrons, 19.21 % for Paracalanus spp. and 39.78 % for E. americana, with site R showing the highest ICM values. The lowest diversity and highest ICM observed in this study could be related to environmental degradation processes, mainly linked to sewage discharge.